Analisis Kebutuhan Video Timeline Berbasis Adobe Premiere Pro untuk Meningkatkan Kemampuan Berpikir Kronologis Siswa dalam Pembelajaran Sejarah - Mariam Jamilah; Ridho Bayu Yefterson (Jurusan Sejarah FIS UNP, 2026)
This study aims to analyze the need for developing learning media in the form of a video timeline based on Adobe Premiere Pro to improve students' chronological thinking skills in history learning at SMA Negeri 1 Banuhampu. The background of this study is the low chronological thinking skills of students, based on pretest results which showed that some students still have difficulty in arranging the sequence of historical events coherently and understanding the relationships between events. In addition, history learning is still dominated by lecture methods and the use of conventional media, so that it does not support students' chronological understanding. This study used a descriptive qualitative method with data collection techniques in the form of observation, interviews, and pretests. The results of the analysis indicate that teachers and students need learning media that are more interactive, contextual, and in accordance with the demands of the Independent Curriculum, especially in developing historical thinking skills. Video timeline media is considered relevant to help students understand the sequence of historical events systematically. Based on the results of this needs analysis, the development of video timeline learning media based on Adobe Premiere Pro is planned as a further stage of research to improve the quality of history learning.